Ecological interaction between Atta sexdens (Hymenoptera: Formicidae) and the vegetation of a mesophyll semideciduous forest fragment in Botucatu, SP, Brazil - Garcia, Ivone P. [UNESP]; Forti, Luiz Carlos [UNESP]; Engel, Vera Lex [UNESP]; De Andrade, Ana Paula P. [UNESP]; Wilcken, Carlos Frederico [UNESP] (My University, 2003)
Among 89 plants species growing in a subtropical dry forest fragment located in Botucatu, State of São Paulo, Brazil, 35 species were cut by Atta sexdens, representing 39.34% of the current plants existing in this area. A. sexdens L., 1758 (Hymenoptera: Formicidae) has a selective preference for the following species: Alchornea triplinervia, Faramea cyanea, Cariniana estrellensis and Casearea obliqua, with the first being the most cut species. The frequency and absolute densities of the plant families and species significantly influence the selection process. When comparing the absolute frequency regarding the 10 most cut plant species and the cutting frequency, significant data were obtained only for the euphorbiaceous A. triplinervia species, proving the preference of A. sexdens for this species in particular. These interactions are discussed based on ecological and management factors in agro-ecosystems.
Keywords: Atta sexdens; Foraging activity; Leaf-cutting ant; Secondary forest; Alchornea; Animalia; Atta; Cariniana estrellensis; Faramea; Formicidae; Hymenoptera